2016
DOI: 10.1177/0022185616648487
|View full text |Cite
|
Sign up to set email alerts
|

Cash for care in Quebec, collective labour rights and gendered devaluation of work

Abstract: Work performed under cash-for-care programmes is based on a relationship between several parties, including, at a minimum, the workers providing the services, the care recipients and the public authorities that manage and fund these programmes. Labour law studies have pointed out that the labour relations regulation is not adapted to this type of non-standard employment relationship since it has been founded on the norm of the integrated firm and bilateral employer–employee relations. Based on a case study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Poor wages can also result in difficulties recruiting workers and high rates of turnover (Patel, 2009) which can affect the quality of care provided (Banerjee et al., 2012). Third, care workers are often undervalued in other ways, including limited access to social protection and opportunities such as training and job mobility (Razavi & Staab, 2010) and weak employment protection (Baines et al., 2016; Boivin, 2016). Studies in high‐income contexts have also found that care workers may be overworked and have little voice within the workplace (Banerjee et al., 2012; Braedley et al., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poor wages can also result in difficulties recruiting workers and high rates of turnover (Patel, 2009) which can affect the quality of care provided (Banerjee et al., 2012). Third, care workers are often undervalued in other ways, including limited access to social protection and opportunities such as training and job mobility (Razavi & Staab, 2010) and weak employment protection (Baines et al., 2016; Boivin, 2016). Studies in high‐income contexts have also found that care workers may be overworked and have little voice within the workplace (Banerjee et al., 2012; Braedley et al., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the Ontario Ministry of Children, Community and Social Services (2019), as of June 2019, there are close to 450,000 beneficiaries (families not individuals) accessing Ontario social assistance. Boivin (2016) and Appay (2005) argue that the carework system, in this case the ECEC system in a neo-liberal market economy "functions even better when the workers' jobs are precarious and their wages depend on the level of activity of the institutions paying them" (p. 496). The low wages and the perpetual lack of respect for the work that educators do, reinforces the devaluation of carework in ECEC.…”
Section: (P 1079)mentioning
confidence: 99%